2011
DOI: 10.1007/978-3-642-24148-2_14
|View full text |Cite
|
Sign up to set email alerts
|

Progress of Commitment in Co-operative Software Acquisition

Abstract: Abstract. This paper reports on the results of a test on a Co-operative Software Acquisition (COSA) model in which the users carry out the ICT investment by themselves. The existing models meant to help in the ICT investments process are too heavy and technical to be used in SMEs. A successful ICT investment is an organisational change process in which people have a critical role. The COSA model applies user participation and team-working in the acquisition of Commercial Off-The-Shelf (COTS) software products.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…Por tal razón, muchas PYMES debido a la falta de recursos internos, incluyendo la falta de conocimientos y habilidades en sistemas de información, recurren a consultores externos para obtener ayuda en los procesos de fortalecimiento tecnológico (Bradshaw, Cragg & Pulakaman, 2012). Sin embargo, es importante considerar que muchas organizaciones fracasan en las inversiones en TIC, lo cual es especialmente cierto en las PYMES, ya que la gestión de las TIC se basa a menudo en una visión de corto plazo y prácticas informales en la toma de decisiones (Rantapuska & Sore, 2011). Debido a esto, se vuelve un factor importante para la gestión de TIC tener en cuenta su eficacia operativa, así como promover su aplicación estratégica para apoyar los procesos de negocio internos (contabilidad, inventarios, compras, ventas, recursos humanos), y los externos (proveedores, clientes, gobierno, socios, etc.)…”
Section: Introductionunclassified
“…Por tal razón, muchas PYMES debido a la falta de recursos internos, incluyendo la falta de conocimientos y habilidades en sistemas de información, recurren a consultores externos para obtener ayuda en los procesos de fortalecimiento tecnológico (Bradshaw, Cragg & Pulakaman, 2012). Sin embargo, es importante considerar que muchas organizaciones fracasan en las inversiones en TIC, lo cual es especialmente cierto en las PYMES, ya que la gestión de las TIC se basa a menudo en una visión de corto plazo y prácticas informales en la toma de decisiones (Rantapuska & Sore, 2011). Debido a esto, se vuelve un factor importante para la gestión de TIC tener en cuenta su eficacia operativa, así como promover su aplicación estratégica para apoyar los procesos de negocio internos (contabilidad, inventarios, compras, ventas, recursos humanos), y los externos (proveedores, clientes, gobierno, socios, etc.)…”
Section: Introductionunclassified
“…On the other hand, the lack of technological skills in the labor force is a major obstacle to the implementation of ICTs, as well as the proliferation of ICT tools and applications, which in recent years has lead SMEs to find it difficult to select the appropriate applications (Evangelista, et al, 2013).Likewise, because SMEs do not have a methodology for Knowledge Management (KM), this implies that decisions are based mainly on tacit knowledge as intuition, experience, attitudes and values. This form of business management, without procedures of knowledge can lead to less success in the implementation of ICTs (Rantapuska and Sore, 2011). They generally take ICTs implementation as any other investment seen only as purchasing tasks, without fully understanding its linkage to the strategy and objectives of the company.…”
Section: Introductionmentioning
confidence: 99%
“…They generally take ICTs implementation as any other investment seen only as purchasing tasks, without fully understanding its linkage to the strategy and objectives of the company. In addition, the investment process in ICT is seen as a technical process and little attention is paid to its organizational nature (Rantapuska, 2011;Chinedu et al, 2014). Although several SMEs are implementing ICTs, it has been found that the majority of them are not making the most of their potential (ANIEI et al, 2011;Estavillo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%